Obstacles to Lifelong Learning in Vietnam and Some Suggested Solutions - Phạm, Đỗ Nhật Tiến (H. : ĐHQGHN, 2017)
Vietnam education is moving on the way of lifelong learning (LLL) development. It has achieved significant progress in broadening the scope of education, diversifying modes of delivery, developing networks of educational institutions throughout the country, and renovating ways of learning. However, evidence shows there are still many weaknesses and shortcomings in the change process, especially in human resources development responding to the socio-economic needs of the country. Taking into account that LLL development is country specific, this article focuses in the analysis of different obstacles, namely conceptual, institutional, structural, financial, and individual obstacles to LLL development in Vietnam. The identification of these obstacles enables to provide solutions for a rationalization of existing LLL system in view of making it function as foundation for the building of a learning society in Vietnam